Government Communication Strategy In Preventing And Reducing The Prevalence Of Stunting In Labuhanbatu Utara District - Samsul Tanjung; Hasan Sazali; Tri Niswati Utami (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
This study aims to analyze and explain the government's communication strategy in the prevention and decline in the prevalence of stunting in North Labuhanbatu Regency. This research is a descriptive qualitative study used to observe the natural conditions of the prevalence of stunting in North Labuhanbatu. This research informant is determined through purposive techniques. This study collects data through semi-structured interviews, non-participant observations, and documentation. This research data refers to primary and secondary concepts, primary data sourced from interviews and observations, while secondary data sourced from relevant journal articles and books. This research data was analyzed through the Miles & Huberman scheme which included reduction, presentation, and data conclusions. The validity of this research data is tested through the degree of trust (credibility), transfer (transferability), dependability, and confirmability. The results of this study indicate that the North Labuhanbatu government implemented a holistic and value-based communication strategy in stunting prevention efforts, by adopting the principles of Islamic communication such as Qaulan Sadidan, Qaulan Layyina, and Qaula Baligha to increase public awareness and participation. This strategy involves synergy between various parties, including local governments, health institutions, non-governmental organizations, and the private sector, with a focus on balanced nutrition education, health education, and successful narratives. Facing challenges such as lack of community understanding, coordination between weak agencies, low literacy, and the lack of participation of community leaders, this strategy emphasizes the importance of integration of stunting prevention programs with other development initiatives, optimization of communication methods, and community involvement in formulating solutions. This comprehensive and integrated approach aims to create a continuous positive impact in reducing the prevalence of stunting and building a healthier future for the people of North Labuhanbatu.